Paleoecology and Geoarchaeology at El Palmar and the El Zotz Region, Guatemala. Issue 1 (25th August 2016) - Luzzadder‐Beach, Sheryl; Beach, Timothy; Garrison, Thomas; Houston, Stephen; Doyle, James; Román, Edwin; Bozarth, Steven; Terry, Richard; Krause, Samantha; Flood, Jonathan
Abstract : A new paleoecology record from the El Palmar Cival adds to the emerging geoarchaeological record of El Zotz, Guatemala. El Palmar's 3 m stratigraphic record began in the Archaic period before 1500 B.C. at or just before initial Maya impacts. From the lowest level, Late Archaic organic deposition, with evidence for diverse tropical forest and a steady water table, transitioned to Early Preclassic clay deposition, decreased forest taxa, three known food taxa, and more economic species. Clay deposition continued through the Preclassic, with occasional organic and high charcoal deposition, increasing maize, and other possible economic pollen. Classic El Palmar saw a new land use type with continued disturbance evidence but diverse and greater forest cover. Human impacts continued, leaving high amounts of disturbance taxa, charcoal, and the highest maize pollen level, concomitant with lower deposition rates, δ 13 C evidence of increased, diverse tropical forest taxa and organic sediments. El Zotz Aguada's Early Classic to Postclassic sediment record overlaps this, with maize and squash pollen evidence changing to Classic period copal tree pollen dominance. Both records indicate the maximum quantity of C4 taxa derived organic matter was about 40%, leaving at least half from C3 taxa such as tropical forest species.